2002
DOI: 10.1016/s0047-2727(00)00160-2
|View full text |Cite
|
Sign up to set email alerts
|

Private costs and public benefits: unraveling the effects of altruism and noisy behavior

Abstract: An increase in the common marginal value of a public good has two effects: it increases the benefit of a contribution to others, and it reduces the net cost of making a contribution. These two effects can be decomposed by letting a contribution have an 'internal' return for oneself that differs from the 'external' return to someone else. We use this framework in a series of one-shot public goods games in which subjects make choices in ten treatments with no feedback. Contributions are generally increasing in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
170
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 220 publications
(190 citation statements)
references
References 11 publications
(10 reference statements)
16
170
1
1
Order By: Relevance
“…Use of PAS is a good choice if the data analysis assumes that subjects are playing a repeated game or if repeated game effects inherent in multiple rounds is effectively controlled. Goeree et al (2002) report an experiment in which subjects make 10 VCM decisions (involving different internal and external marginal return rates) without feedback. PORnp was used for payoff from the VCM rounds.…”
Section: Examples Of Experiments On Public Goods and Votingmentioning
confidence: 99%
“…Use of PAS is a good choice if the data analysis assumes that subjects are playing a repeated game or if repeated game effects inherent in multiple rounds is effectively controlled. Goeree et al (2002) report an experiment in which subjects make 10 VCM decisions (involving different internal and external marginal return rates) without feedback. PORnp was used for payoff from the VCM rounds.…”
Section: Examples Of Experiments On Public Goods and Votingmentioning
confidence: 99%
“…We also report the average contributions as a percentage of endowments and levels of statistical significance. 5 With the exception of Goeree et al (2002) who use one-shot games, all studies use repeated VCM games. In most studies group composition does not change across periods (partners matching protocol).…”
Section: Group Size Effects In Previous Vcm Experimentsmentioning
confidence: 99%
“…Group size effects are studied by varying the number of players matched in a group. In all studies group sizes are varied in a between-subject design, except in Goeree et al (2002) who use a within-subject design. Most studies have investigated group size effects using groups of 4 or more players.…”
Section: Group Size Effects In Previous Vcm Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…These experiments, typically conducted on the fundamental social dilemmas such as the Prisoner's dilemma, the Traveler's dilemma, and the Public Goods game, have shown that cooperation between players (associated with the deviation from the unique, but inefficient, Nash equilibrium) is frequent, and appears to depend on both the game parameters and the environment in which the game is played. In particular, it has been observed that the rate of cooperation in the Traveler's dilemma depends on the bonus/penalty value, whenever the game is single-shot or iterated [7], [12]; the rate of cooperation in the Prisoner's dilemma depends on the payoff parameters or the way the players are matched to play together [11], [32]; and the rate of cooperation in the Public Goods game depends on the marginal return or on the frequency of interaction between free-riders and cooperators [13], [14] [17].…”
Section: Introductionmentioning
confidence: 99%